Quality of life and anxiety in children and adolescents in residential treatment facilities. Issue 3 (3rd July 2019) - Molinari, Arielle D.; Andrews, Jessica L.; Zaboski, Brian A.; Kay, Brian; Hamblin, Rebecca; Gilbert, Alexandra; Ramos, Amaya; Riemann, Bradley C.; Eken, Stephanie; Nadeau, Joshua M.; Storch, Eric A.
ABSTRACT: Anxiety-related impairment among youth in residential treatment facilities is common, but quality of life (QOL) among this intensive, treatment-seeking population remains largely unexplored. The purpose of this study was to investigate factors that decrease QOL among children/youth with severe anxiety disorders. Specifically, this research studied whether comorbid depression would negatively impact QOL and whether depression would predict QOL above and beyond the effects of anxiety. Depression symptomology as a potential moderator variable for QOL was also analyzed, as well as the effect of multimodal treatment on QOL. Analyses revealed that parent- and child-rated measures had different predictive utility when investigating QOL, but that depression predicted poorer QOL than anxiety. No moderation effect for depression was found. Lastly, multimodal treatment was effective in improving quality of life (d = 1.30) for treatment responders. Clinical and research implications are discussed.